Immigrants' electoral participation – the cross-national impact of public and political hostility. Issue 15 (17th November 2020) - Tyrberg, Maria
ABSTRACT: While we know that anti-immigrant attitudes are widely expressed in the public opinion and through parties aiming to limit immigration and migrant rights within European countries, we know less about the effects of such contextual hostility on immigrants, the targeted group. Making use of the cross-national variation of anti-immigrant attitudes and anti-immigrant party strength, my study tests the impact of public and political contextual hostility on voting among citizens in 28 countries. Results from multilevel modelling show that anti-immigrant attitudes in the public to some extent increases voting among citizens with the immigrant background in comparison to natives, indicating a mobilising influence of contextual hostility within the targeted group. The mobilising effect is however not found in countries with the highest levels of anti-immigrant attitudes, or when measuring hostility with anti-immigrant party parliamentary representation. In addition, I find an unexpected negative effect of public contextual hostility on voting among natives, suggesting a strong demobilising influence of hostility within the native group.